Study of dynamic behaviour of multi-layered structures subjected to blast loading - Ahmad, Muhammad Saeed (Department of Mechanical Engineering, 2014)
The objective of this research work is to assess the response of multi-layered plates in comparison to single plates to gain physical understanding of different phenomena taking place at micro level during localized blast loading. Since layered plates have been shown to give improved ballistic performance under certain circumstances, it is useful to ascertain and understand the influence of layering on blast performance. This investigation is carried out both experimentally and numerically. A finite element model was developed to design the blast experiments for two different steels of various thicknesses.